2022
DOI: 10.1002/ecy.3808
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and observational evidence of negative conspecific density dependence in temperate ectomycorrhizal trees

Abstract: Conspecific negative density dependence (CNDD) promotes tree species diversity by reducing recruitment near conspecific adults due to biotic feedbacks from herbivores, pathogens, or competitors. While this process is well-described in tropical forests, tests of temperate tree species range from strong positive to strong negative density dependence. To explain this, several studies have suggested that tree species traits may help predict the strength and direction of density dependence: for example, ectomycorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Mutualistic AM fungi are also thought to be important in influencing CDD and seedling performance (Bever, 2002; Mangan et al, 2010b; Bachelot et al, 2015; Liang et al, 2015; Bachelot et al, 2017; Bennett et al, 2017; Jevon et al, 2022). We hypothesized that the repeated input of conspecific seeds and/or seedlings near female trees would result in more opportunities for the growth of AM fungi, and subsequently, higher colonization rates by AM fungi in seedlings grown in female conspecific soils relative to male soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutualistic AM fungi are also thought to be important in influencing CDD and seedling performance (Bever, 2002; Mangan et al, 2010b; Bachelot et al, 2015; Liang et al, 2015; Bachelot et al, 2017; Bennett et al, 2017; Jevon et al, 2022). We hypothesized that the repeated input of conspecific seeds and/or seedlings near female trees would result in more opportunities for the growth of AM fungi, and subsequently, higher colonization rates by AM fungi in seedlings grown in female conspecific soils relative to male soils.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of negative CDD may be driven by plant–soil feedbacks between established plants and host-specific pathogenic soil microbes that negatively influence seedling performance (reviewed by Kulmatiski et al, 2008; van der Putten et al, 2013). Variation in negative CDD is often quantified among co-occurring plant species and attributed to differences in species’ life history strategies and related traits (Kobe & Vriesendorp, 2011; Lebrija-Trejos et al, 2016; Zhu et al, 2018; Jia et al, 2020; Zang et al, 2021), species relative abundance (Comita et al, 2010), or mycorrhizal associations (Bennett et al, 2017; Jiang et al, 2020; Jevon et al, 2022). Though experiments have shown that variation in seedling performance near conspecifics may also occur within species (Packer & Clay, 2003; Hood et al, 2004; Bell et al, 2006; Eck et al, 2019), the factors that contribute to intraspecific variation in conspecific neighbor effects are rarely studied (Freckleton & Lewis, 2006; but see Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutualistic AM fungi are thought to be important in driving PSFs and seedling performance, alongside pathogens (Bever 2002, Mangan et al 2010a, Bachelot et al 2015 2017, Liang et al 2015, Bennett et al 2017, Jevon et al 2022). Studies with other dioecious species show that individuals of different sexes can form different associations with AM fungi (Varga and Kytöviita 2008, 2008, b2010b, Eppley et al 2009, Vega‐Frutis et al 2013), but it is unclear what consequences this variation might have in natural plant populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pathogenic microbes, co‐occurring mutualists are also important in generating PSFs (Bever 2002, Mangan et al 2010a, Bachelot et al 2015, Teste et al 2017; reviewed by Revillini et al 2016) but are underexplored in relation to dioecy. Arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) fungi can have variable effects on conspecific seedling growth and species coexistence (Bever 2002, Castelli and Casper 2003, Liang et al 2015, Bennett et al 2017, Koziol and Bever 2018, Liang et al 2020, Jevon et al 2022). Positive PSFs, often caused by the accumulation of host‐specific mutualistic microbes such as AM and ECM fungi in the soils near adult plants, result in increased performance of seedlings in conspecific soils relative to heterospecific soils (Smith and Reynolds 2012, Reinhart et al 2012, Teste et al 2017, Segnitz et al 2020, Duell et al 2023).…”
Section: Introductionmentioning
confidence: 99%